Sexual Harassment and its Effects on the Mental Health of the Adolescents School Girls in Lalitpur and Rupandehi District - Gyawali, Kalpana (Tribhuvan University Journal, 2020)
A cross-sectional study was conducted to find the prevalence of mental health on adolescent girl students and the effect of sexual harassment on their mental health: depression, anxiety, and stress. A concurrent mixed method was used and the study was conducted at both community and institutional schools of Lalitpur and Rupendehi districts. A semi-structured questionnaire was used for quantitative data collection along with depression, anxiety and stress score test (DASS -42 points) to measure depression, anxiety, and stress. Focus group discussion (FGD), in-depth interviews (IDI), and key informant information (KII) were used for qualitative data collection. Poor and ill mental health were found among the respondents and the prevalence of depression, anxiety and stress were45%, 52%, and 35% respectively among the sexually harassed girls. As sexual harassment was found as one of the major factors that is responsible for the poor mental health status of girl students, it is necessary for every school to adopt antisexualharassmentpoliciesandtotakeactionagainstittocreateahealthylearningenvironment.